2019
DOI: 10.1016/j.hrthm.2018.10.018
|View full text |Cite
|
Sign up to set email alerts
|

CHA2DS2-VASc scores and Intermountain Mortality Risk Scores for the joint risk stratification of dementia among patients with atrial fibrillation

Abstract: BACKGROUND High CHA 2 DS 2-VASc scores in atrial fibrillation (AF) patients are generally associated with increased risks of stroke and dementia. At lower CHA 2 DS 2-VASc scores, there remains an unquantifiable cranial injury risk, necessitating an improved risk assessment method within these lower-risk groups. OBJECTIVE The purpose of this study was to determine whether sex-specific Intermountain Mortality Risk Scores (IMRS), a dynamic measures of systemic health that comprises commonly performed blood tests,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…The composite IMRS, when separated into three risk categories (low, moderate, high), individually predict risk of incident dementia in both men and women. [42] These scores also segregate risk across all CHA 2 DS 2 -VASc scores highlighting the value of understanding physiology in the setting of baseline risk. [43] The same value of IMRS can be seen in better discerning risk of stroke, as the IMRS improves the C-statistic when combined with CHADS 2 and CHA 2 DS 2 -VASc scores in both men and women.…”
Section: Improving Risk Prediction Of Cognitive Decline In Patients Wmentioning
confidence: 99%
“…The composite IMRS, when separated into three risk categories (low, moderate, high), individually predict risk of incident dementia in both men and women. [42] These scores also segregate risk across all CHA 2 DS 2 -VASc scores highlighting the value of understanding physiology in the setting of baseline risk. [43] The same value of IMRS can be seen in better discerning risk of stroke, as the IMRS improves the C-statistic when combined with CHADS 2 and CHA 2 DS 2 -VASc scores in both men and women.…”
Section: Improving Risk Prediction Of Cognitive Decline In Patients Wmentioning
confidence: 99%
“…Further, the data are easily integrated into computerized decision support systems (the IMRS is presently calculated automatically and displayed in our electronic medical record for every patient admitted to any of our 23 hospitals). While designed to predict mortality, the IMRS has shown surprising ability to predict outcomes in several disease states, such as heart failure, 23 dementia, 27 stroke, 29 and trauma mortality 26 . Unfortunately, this utility does not appear to extend to HA‐VTE.…”
Section: Discussionmentioning
confidence: 99%
“…22 The score has been further refined and validated among outpatient, inpatient, cardiovascular, trauma, and other medical populations. [23][24][25][26] Additional outcomes predicted by variations of the Intermountain Risk Score (IMRS) include heart failure, 23 dementia, 27 chronic cardiopulmonary disease, 28 and stroke. 27,29 Likewise, the longitudinal predictive value of the IMRS has been demonstrated with serial measurements at baseline and at 1 year of follow-up and shown to be independently prognostic for mortality and heart failure among initially hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same investigators launched another very large study (including 34 083 women and 39 998 men with AF and no history of dementia) to determine whether sex-specific Intermountain Mortality Risk Scores (IMRS), a dynamic measure of general health that includes commonly performed blood tests (glucose level, mean corpuscular volume, red cell distribution width, calcium level for women plus age, calcium and sodium levels, hematocrit, and red cell distribution width for men), can stratify dementia risk overall and among CHA 2 DS 2 -VASc score strata in patients with AF. 92 They found that high-risk IMRS patients were generally older and had higher rates of hypertension, heart failure, prior stroke, and diabetes. Higher CHA 2 DS 2 -VASc score strata (≥3 vs ≤ 1; women, HR: 7.77, 95% CI: 5.94-10.17, P < .001; men, HR: 4.75, 95% CI: 4.15-5.44, P < .001) and IMRS categories (high vs low: women, HR: 3.09, 95% CI: 2.71-3.51, P < .001; men, HR: 2.70, 95% CI: 2.39-3.06, P < .001) were predictive of dementia.…”
Section: Risk Factors and Markersmentioning
confidence: 99%